2014
DOI: 10.1002/acp.3048
|View full text |Cite
|
Sign up to set email alerts
|

Attorneys' Questions and Children's Productivity in Child Sexual Abuse Criminal Trials

Abstract: Summary We investigated the links between questions child witnesses are asked in court, children’s answers, and case outcome. Samples of acquittals and convictions were matched on child age, victim–defendant relationship, and allegation count and severity. Transcripts were coded for question types, including a previously under-examined type of potentially suggestive question, declarative questions. Children’s productivity was conceptualized in a novel way by separating new from repeated content and by adjustin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 45 publications
(38 reference statements)
7
100
3
Order By: Relevance
“…Unfortunately, the Court did not report how the child was asked about clothing. Research examining how children are questioned about sexual abuse in court has shown that yes/no questions predominate (Andrews, Lamb, & Lyon, ; Hanna, Davies, Crothers, & Henderson, ; Klemfuss, Quas, & Lyon, ; Stolzenberg & Lyon, ). Hence, it is likely that the child in Emmett was asked yes/no questions about his and the defendant's clothing placement (e.g., ‘Were your/his clothes on?’ or ‘Were your/his clothes off’?…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the Court did not report how the child was asked about clothing. Research examining how children are questioned about sexual abuse in court has shown that yes/no questions predominate (Andrews, Lamb, & Lyon, ; Hanna, Davies, Crothers, & Henderson, ; Klemfuss, Quas, & Lyon, ; Stolzenberg & Lyon, ). Hence, it is likely that the child in Emmett was asked yes/no questions about his and the defendant's clothing placement (e.g., ‘Were your/his clothes on?’ or ‘Were your/his clothes off’?…”
Section: Introductionmentioning
confidence: 99%
“…(Results concerning the frequency of attorneys' use of the different question types can be found in Klemfuss et al . ().) In other words, of interest was whether, for example, temporal structure was consistently higher when WH questions were asked (as might be expected from forensic interviewing protocols) and lower when suggestive questions were asked.…”
Section: Resultsmentioning
confidence: 99%
“…Namely, prosecutors are invested in highlighting children's strengths as witnesses and encouraging them to provide the details of their experiences when those details best contribute to the child's allegation. Given that previous research has demonstrated that defence attorneys also provide less structure for children through the types of questions asked (e.g., more suggestive, fewer WH; Klemfuss et al ., ; Mueller & Kirkpatrick, ; Zajac & Hayne, ; Zajac et al ., ) and that these question types are largely independent of provision of temporal structure, child witnesses may be at a double disadvantage when being questioned by defence attorneys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations